Actinobacteria From Desert: Diversity and Biotechnological Applications - Xie, Feiyang; Pathom-aree, Wasu (Frontiers in Microbiology, 2021)
Desert as an unexplored extreme ecosystem, is known to harbour diverse actinobacteria with biotechnological potential. Both multidrug-resistant (MDR) pathogens and environmental issues have sharply raised the emerging demand for functional actinobacteria. From 2000 to 2021, 129 new species have been continuedly reported from 35 deserts worldwide. The two largest numbers are members of genera Streptomyces and Geodermatophilus, and other functional extremophilic strains such as alkaliphiles, halotolerant, thermophiles and psychrotolerants. The improved isolation strategies for the recovery of culturable and unculturable desert actinobacteria are crucial for the exploration of their diversity and offer a better understanding of their survival mechanisms under extreme environmental stresses. The main bioprospecting processes involve isolation of target actinobacteria on selective media, incubation and selection of representatives from isolation plates for further investigations. Bioactive compounds obtained from desert actinobacteria are being continuedly explored for their biotechnological potential, especially in medicine. To date, there are more than 50 novel compounds were discovered from these gifted actinobacteria with potential anti-microbial activities, including anti-multidrug-resistant pathogens, anti-inflammatory, anti-virus, anti-fungal, anti-allergic, anti-bacterial, anti-tumour and cytotoxic activities. A range of plant growth-promoting abilities of the desert actinobacteria inspired the great interest in their agricultural potential. In addition, several degradative, oxidative and other functional enzymes from desert strains can be applied in industry and the environment. This review aims to provide a comprehensive overview of desert environments as a remarkable source of diverse actinobacteria while such rich diversity offers an underexplored resource for biotechnological exploitations.